ASSESSMENT OF DEMOGRAPHIC INDICATORS CHARACTERIZING REPRODUCTION OF THE POPULATION OF THE KRASNODAR TERRITORY - T. A. Shiltsova; V. V. Pilshchikova; Yu. A. Vasiliev (Новые технологии)
The article discusses the priorities of the state policy in the field of stabilization of demographic processes aimed at a significant increase in the birth rate. An aging population, a drop in the birth rate determine today the interest in family support and in the birth of a second and third child are the basis of the country's social policy.Statistical data that characterize the state of reproduction of the population are usually attributed to demographic indicators. Such indicators as birth rate, mortality, indicators of the size and structure of the population are extremely important ones for the natural movement of the population. Evaluation of demographic indicators in terms of population reproduction has revealed a steady decline in the total fertility rate and the total birth rate. The basis of this process is an objective reduction in the share of the reproductive contingent of women and the «aging» of the population. Evaluation of the order of birth indicates the effect of «delaying" the birth of the first child. The revealed trends in the dynamics of the modern demographic situation in the Krasnodar Territory indicate the processes of demographic «failure» in groups of active fertile age, «aging» of the age-specific fertility model, and a significant reduction in the number of births. The results of the assessment of the potential of the demographic situation of the region made it possible to develop proposals for increasing the reproduction of the population.